Analisis Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Kurir Narkotika (Studi Putusan Perkara Nomor : 414/PID-Sus/2014/PN.Kla) - Zainab Ompu Jainah (KEADILAN PROGRESIF, 2016)
Circulation of Narcotics in Indonesia today has manifested in various forms since the Narcotics traffickers always find a loophole to run the circulation of narcotics. One case is the crime of illicit traffic of narcotics in the jurisdiction of the District Court Trump in Decision Case Number: 414 / Pid-Sus / 2014 / PN.Kla, defendant Syarbaini Bin M. Dahlan proven legally and convincingly guilty of committing a crime do conspiracy unlawfully or unlawfully receiving Narcotics Group I in plants not exceeding five (5) grams. The main problem in this study include: a. What form criminal liability courier Narcotics, The study was conducted with normative and empirical approach. The data used in this study secondary and fiel study the data was analyzed qualitatively. The conclusion of this study are:  criminal liability that is based on the courier Narcotics errors that meet the elements against the law and there is no reason for removing the unlawful nature of the actions performed. Executed criminal liability of punishment against the defendant for 15 (fifteen) years imprisonment and a fine of Rp. 1.000.000.000, - (one billion rupiah) provided that if the defendant can not afford to be replaced by imprisonment for six (6) months. Suggestions in this study so that law enforcement officials should determine and follow up on the crime of Narcotics courier in the event of a deed investments / participating or participated stand alone.